PENGUKURAN KINERJA SISTEM INFORMASI MENGGUNAKAN BALANCE SCORECARD - Michael Iskandar (Center for Economic Studies Universitas Katolik Parahyangan, 2007)
The balanced scorecard (BSC) is a method created bt Kaplan and Norton to fulfill the needs of modern corporations for performance evaluation. As it turns out, BSC is not appropiate for evaluation, but also an effective tool for the creation of corporate strategy as well as communicating it throughout the company. On the other hand, information resources nowadays are admitted to be a strategic value to the firm, and should be optimally managed. This paper describes how BSC may be applied to the effort of managing the firm's information systems, including its perfomance measurement